Невропсихолошко-динамски приод кон развојната психотична дисхармонија - Копачев, Драгослав; Трајковски, Владимир (Филозофски факултет, Скопје, 2000)
Based on a case from the clinical praxis, the authors, adopting a neuropsychological attitude, study and define the developmental disharmony of a psychotic type. They consider that the developmental disharmony of a psychotic type represents a global profound destruction of the structures and functions (motorics, speech, emotions, cognition, and socialization). The foundation thesis is that in the basis of the disharmony developmental structure of the child. „А psychotic nucleus“ is being rather early in the age of the child development, with under pressure of the not favorable environmental factors leads to psychotic manifestation of the personality. The developmental disharmony of a psychotic type could have a various outcome. The child could manifest a progressive deteorisation, to involve in a direction of schizophrenic psychoses, to structure itself as a „Borderline“ personality, with very rarely relative normalization of the personality could occur. The authors promote the significance of early detection, qualitative diagnostic and adequate treatment by well educated and poivalent, multidisciplinary experts team.
Developmental Disharmony of Psychotic Type Overview from a Neuropsychological Aspect
Keywords: развојна психотична дисхармонија, первазивно растројство, атипичен аутизам, невропсихолошко-динамска анализа